Advances in master planning of urban underground space (UUS) in China. (May 2016) - Zhao, Jing-Wei; Peng, Fang-Le; Wang, Tian-Qing; Zhang, Xiao-Yun; Jiang, Bing-Nan
Highlights: The background of urban underground space (UUS) development in China is analyzed. The contents of master planning of UUS is presented. The characteristics of master planning of UUS is analyzed. Overall layout methods for UUS is obtained. Related theories and methods are applied in the master planning of UUS for Qingdao. Abstract: Following economic growth and urban development in China in the past two decades, rapid urbanization have incurred many pronounced problems to many Chinese cities. Since 2000, key areas in many Chinese cities, drawing on valuable urban development experience from America and European countries, flock to conduct master planning of urban underground space (UUS) development. The compiling practice is conducive to the orderly development of urban space and alleviation of increasing human-land conflicts. Through selecting and analyzing the master planning UUS in Qingdao, this paper first investigates the current problems of UUS development and utilization in China, and then analyzes the planning methods and general thoughts of overall underground space layout. In general, the paper presents some current advanced research findings in the master planning of UUS development in China.